Diagnosis of Kidney Disease Through the Image of the Iris Eye Using the Method of Segmentation Edge Detection Techniques - Sony Teguh M; Laras Niti M; Rizky Febri S (Prosiding International conference on Information Technology and Business (ICITB), 2017)
Iridology as a science is based on an analysis composition of iris. In particular organ rather iris have specific advantages, which can record all the conditions of the organs, body construction, as well as psychological conditions. Trace records related to the intensity levels or deviations organs caused by disease recorded in a systematic and patterned on the iris of the eye and surrounding area. It can be used as a practical guideline for the diagnosis of the various diseases. Therefore, further research needs to be done about the condition of the organ diagnosis by looking at image of the iris. In this research, the software is able to perform classification using edge detection and segmentation floating. Eye image to be processed first separated from the image of the eye and then changes to the gray level image and the image quality improvement using adaptive histogram. The next process is to change the image of iris into rectangular form and making the Region Of Interest eye image associated with the kidneys, the last step is to detect the edge of the iris image ROI, and turn it into a binary image for the calculated area of wounds on iris image ROI. From the test results, it can be concluded that the iris recognition system shows good recognition results. There are several factors that influence the recognition process Noise of the input image, color image of the iris of the eye, the lighting in the input image. Of 20 tested iris image, the program can recognize 19 of image, so the program can recognize of 95%. Keyword :   Iridology, digital image processing, edge detection.